An overview of forecasting facing breaks - Castle, J; Hendry, D; Clements, M (University of Oxford, 2016)
Economic forecasting may go badly awry when there are structural breaks, such that the relationships between variables that held in the past are a poor basis for making predictions about the future. We review a body of research that seeks to provide viable strategies for economic forecasting when past relationships can no longer be relied upon.